1990
DOI: 10.1111/j.1469-8137.1990.tb00482.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of soil water potential on seed germination of some British plants

Abstract: Seeds' of 15 species collected from a range of habitats contrasting in soil water status were germinated in soils of known matric potentials ranging from near field capacity to the permanent wilting potential ( -0-05, -0-5, -1-0 and -1-5 MPa). Germination was very sensitive to soil water potential and species responded in various ways. Some showed germination responses which correlated with the soil water status of their native habitat: none of the wetland species studied could germinate to any great extent at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
134
1
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(154 citation statements)
references
References 29 publications
(21 reference statements)
15
134
1
2
Order By: Relevance
“…Additionally, dry periods during the rainy season may influence recruitment patterns in gaps through effects on seed germination and initial seedling emergence. Soil water potentials that are similar to or higher than those measured in this experiment are sufficient to significantly reduce seed germination rates in pioneer species (Evans and Etherington 1990;Daws et al 2002), and germination sensitivity to soil water potentials shows strong interspecific variation (Daws et al 2002). We expect that the vulnerability of pioneer seedlings to wet-season drought decreases once they have made it through the initial tiny stages, and have developed a root system extending to soil layers not affected by superficial drying processes (Fig.…”
Section: Drought In Tropical Forestsmentioning
confidence: 99%
“…Additionally, dry periods during the rainy season may influence recruitment patterns in gaps through effects on seed germination and initial seedling emergence. Soil water potentials that are similar to or higher than those measured in this experiment are sufficient to significantly reduce seed germination rates in pioneer species (Evans and Etherington 1990;Daws et al 2002), and germination sensitivity to soil water potentials shows strong interspecific variation (Daws et al 2002). We expect that the vulnerability of pioneer seedlings to wet-season drought decreases once they have made it through the initial tiny stages, and have developed a root system extending to soil layers not affected by superficial drying processes (Fig.…”
Section: Drought In Tropical Forestsmentioning
confidence: 99%
“…Results showed that provenance 2 had a higher germination percentage of the stressed seeds at -0.03 MPa compared with non-stressed seeds. Seed germination percentage and Kotowski's coefficient generally decrease as soil water potential decreases (Evans, Etherington, 1990;Oberbauer, Miller, 1982), either by drought or by higher salinity. By increasing water stress, similar results were found on germination of Diospyros texana seeds that decreased from about 95% to 45% at 0 and -0.6 MPa, respectively (Everitt, 1984), whereas germination of three deciduous semi-shrubs of genus Artemisia was inhibited severely in PEG 6000 solutions at -1.…”
Section: Salinity and Drought Treatmentsmentioning
confidence: 99%
“…» Germination and seedling survival are the next 'sieves' in the life history of plants by which hydrology might play a structuring role in vegetation develop ment (Keddy & Ellis, 1985;Moore & Keddy, 1988 (Hürlimann, 1951;Van der Toorn, 1972;Haslam, 1973;Rodewald-Rudescu, 1974), Phalaris arundinacea (Junttila, Landgraff & Nilsen, 1978), S. lacustris (Seidel, 1955) and Typha spp. (Yeo, 1964;Bedish, 1967;Grace & Harrison, 1986;Frankland, Bartley & Spence, 1987;Evans & Etherington, 1990). On exposed soil surfaces, moisture availability in the germination period depends not only on the groundwater level, but is correlated with the particle size of the sediment as well (Keddy & Constabel, 1982).…”
Section: Seeds Of Scirpus Lacustrismentioning
confidence: 99%